2020
DOI: 10.1111/ijcp.13481
|View full text |Cite
|
Sign up to set email alerts
|

A simple prognostic score predicts one‐year mortality of alert and calm emergency department patients: A prospective two‐center observational study

Abstract: Study Objective To derive and validate a prognostic score to predict 1‐year mortality using vital signs, mobility and other variables that are readily available at the bedside at no additional cost. Methods Post hoc analysis of two independent prospective observational studies in two emergency departments, one in Denmark and the other in Switzerland. Participants Alert and calm emergency department patients. Measurements The prediction of mortality from presentation to 365 days by vital signs, mobility and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…The primary endpoint was 1‐year all‐cause mortality. Data on all‐cause mortality at the 1‐year follow‐up were collected using a combination of electronic health records, official registries, insurance data, contact with patients, primary care physicians or patients' proxies as previously demonstrated 4 . Sufficient power for our analysis was targeted at an inclusion of 2100 patients, including 5% for missing data 35,36 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary endpoint was 1‐year all‐cause mortality. Data on all‐cause mortality at the 1‐year follow‐up were collected using a combination of electronic health records, official registries, insurance data, contact with patients, primary care physicians or patients' proxies as previously demonstrated 4 . Sufficient power for our analysis was targeted at an inclusion of 2100 patients, including 5% for missing data 35,36 …”
Section: Methodsmentioning
confidence: 99%
“…Longer term prognostication is likely more dependent on physiological reserve such as the degree of frailty rather than how ill or seriously injured the patient was at ED presentation 4 . Such prognostication is relevant as accurate predictions empower more informed shared decision‐making, 5,6 and should ideally encompass the period of acute illness or injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was based on previous safety data regarding informal triage and physiological reserve (e.g., mobility). In detail, unimpaired mobility, low physician disease severity ratings (PDSR), and normal vital signs are associated with a very favorable prognosis [ 3 , 4 , 5 , 6 , 7 ]. We hypothesized that these principles hold true for a coordinated large-scale testing process.…”
Section: Introductionmentioning
confidence: 99%
“…A number of prognostic scores have been developed with the goal of identifying those patients who are safe to discharge from the Emergency Department (ED). 17,18 Chang et al 19 recently reported that even minor abnormalities in physiology (vital signs -heart or respiratory rate and blood pressure) at presentation to the ED were predictive of early death, but with considerable overlap to others who did not suffer an early death. Patients with Major Disease Categories (MDCs) of malignant neoplasm, coronary heart disease, chronic obstructive pulmonary disease, congestive heart failure or neurological disease, had a greater likelihood for early death following an ED visit.…”
Section: Introductionmentioning
confidence: 99%